1975
DOI: 10.1159/000231295
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Reaginic Antibody Formation in the Mouse by Concanavalin A

Abstract: SWR mice injected with Concanavalin A (Con A) and Ovalbumin (Ov) one immediately after the other or with mixtures of Con A and Ov produced reaginic antibodies to Ov (titer 1:80) after primary immunization and reaginic antibody levels of 1:640 after secondary immunization. Mixtures of Con A and Ov were shown to contain soluble complexes which could be precipitated by 20% polyethylene glycol (PEG). Mixtures of Con A and human serum albumin or Con A. and bovine serum albumin did not form soluble complexes and did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…The effectiveness of Con A as an allergen did lead us to test, and to discard, the no tion that allergens were mitogens (see 'In troduction'). Con A may simply be useful in inducing IgE responses to complexed [11] or conjugated antigens or haptens. The po tency of Con A as an allergen certainly indi cates that laboratory personnel working reg ularly with Con A are made aware of the possibility of becoming sensitized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of Con A as an allergen did lead us to test, and to discard, the no tion that allergens were mitogens (see 'In troduction'). Con A may simply be useful in inducing IgE responses to complexed [11] or conjugated antigens or haptens. The po tency of Con A as an allergen certainly indi cates that laboratory personnel working reg ularly with Con A are made aware of the possibility of becoming sensitized.…”
Section: Discussionmentioning
confidence: 99%
“…One of these, the potent mitogen concana valin A (Con A), was found to be particu larly effective at inducing anti-Con A re agins in some mouse strains. In addition, Gollapudi and Kind [11,12] have shown that Con A complexed to ovalbumin in creases the allergenicity of ovalbumin. These observations prompted us to examine whether purified allergenic preparations from the nematode, Ascaris suum, and rye grass pollens were mitogenic.…”
Section: Introductionmentioning
confidence: 99%
“…In previous publications we have demon strated that mixtures of concanavalin A (Con A) and ovalbumin (Ov) are powerful inducers of reaginic antibodies to Ov in many strains of mice [1,2]. The exact mechanism of the adjuvant-like effect of Con A was not determined although it was considered that the ability of Con A to acti vate T lymphocytes and to form soluble complexes with Ov were important factors in its action [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The exact mechanism of the adjuvant-like effect of Con A was not determined although it was considered that the ability of Con A to acti vate T lymphocytes and to form soluble complexes with Ov were important factors in its action [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation